STUDENTS' SELF-ASSESSMENT IN PRE-CLINICAL AND CLINICAL EDUCATION OF PROSTHETIC DENTISTRY - Dimiter Kirov; Stefka Kazakova; Janet Kirilova (Peytchinski Publishing, 2014)
Background: The ability to self-assess is a critical skill that all health professionals must be able to do, in order to achieve competence. This is essential for the doctors of dental medicine. During their education and practice they apply different clinical and para-clinical procedures. The aim is to evaluate the students' self-assessment skills during the education of clinic and pre-clinic of prosthetic dentistry. Material and methods: After the completion of certain work - preparation for full veneer crown, a questionnaire was provided to each student in preclinical course (n=30) and clinical course (n=30) for self-evaluation. The questionnaire involved: axial reduction, occlusal reduction, facial and lingual reduction, smoothing and finishing. The answers were based on the standard for the university grading scale. Than, the same questionnaire was fulfilled by the assistant professor without seeing students' self-evaluation. Results and Discussion: Results have been reported in percentages. 100% respond rate has been achieved. The students from the preclinical course tend to overestimate their performance (50%). The students from the clinical course tend to submit overall lower grades than the faculty evaluation (25%). Conclusions: The students from clinics have better self-assessment skills. The discrepancy was most pronounced in the junior students. The different evaluations (self-assessment and assistant professor's) help students to improve their understanding of certain principles and improve the teaching effectiveness of education of prosthetic dentistry.